2013
DOI: 10.3126/kumj.v10i3.8021
|View full text |Cite
|
Sign up to set email alerts
|

Depression Among Undergraduate Medical Students

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
66
6
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 18 publications
13
66
6
6
Order By: Relevance
“…Our results for gender are consistent with the results of the study by Basnet (18), which reported a prevalence of depression of 32.43% among female students versus 28.07% in male students (19). In the study in Rafsanjan, using the SCL-90-R questionnaire, the prevalence of symptoms associated with mental disorders was 21.6% among females and 10.6% among males (15).…”
Section: Discussionsupporting
confidence: 91%
“…Our results for gender are consistent with the results of the study by Basnet (18), which reported a prevalence of depression of 32.43% among female students versus 28.07% in male students (19). In the study in Rafsanjan, using the SCL-90-R questionnaire, the prevalence of symptoms associated with mental disorders was 21.6% among females and 10.6% among males (15).…”
Section: Discussionsupporting
confidence: 91%
“…[13] Though it was not statistically significant, the prevalence of severe and extreme depression was higher in males (61.1% and 58.3% respectively) as compared to females (38.9% and 41.7%, respectively). This is similar to a study by Kumar and Jain, which showed a higher prevalence of depression in males.…”
Section: Depressionmentioning
confidence: 73%
“…Psychological stress associated with depression is common among medical students and considered as an important indicator for mental health [1]. Such mental disorders might lead to numerous undesirable personal and professional consequences such as; growing cynicism, substance abuse, smoking, alcohol consumption, and social isolation [2].…”
Section: Introductionmentioning
confidence: 99%